A proposal for a syntactic solution of the problems of disjunction in human thought - López Astorga, Miguel (Praxis Filosófica, 2017)
The mental logic theory does not accept a rule correct in standard propositional calculus: the disjunction introduction rule (that is, the rule that allows inferring, for example, p or q from p). This is a problem because that very theory admits another schema in which the rule is really involved. It is true that, as shown by López-Astorga, the mental logic theory can be updated following recent empirical results and that such an update can help the theory solve some of its difficulties. However, López-Astorga’s update does not address the challenges directly raised by the disjunction introduction rule, and this paper is intended to do so. In particular, my thesis here is that all of the difficulties of the aforementioned rule can disappear if it is considered to be not a Core Schema of the human syntax of thought, but a Feeder Schema of it.